2014
DOI: 10.1002/cplu.201402275
|View full text |Cite
|
Sign up to set email alerts
|

DNA Targeting by Cationic Porphyrin–Ruthenium(II) Conjugates

Abstract: Scheme 2. Synthesis of P5: [Ru ([9]aneS3)(dmso)Cl 2 ], CH 3 OH/CH 2 Cl 2 6:1, heated at reflux, 24 h (71 %).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…DNA is also one of the most specific biological targets for cationic porphyrins. The formation of strong complexes of these compounds with nucleic acids has been reported, including for the recognition of noncanonical structures of DNA called G-quadruplexes [ 41 ]. Other authors [ 42 ] have shown that the HSV-1 genome contains multiple clusters of repeated G-quadruplex.…”
Section: Introductionmentioning
confidence: 99%
“…DNA is also one of the most specific biological targets for cationic porphyrins. The formation of strong complexes of these compounds with nucleic acids has been reported, including for the recognition of noncanonical structures of DNA called G-quadruplexes [ 41 ]. Other authors [ 42 ] have shown that the HSV-1 genome contains multiple clusters of repeated G-quadruplex.…”
Section: Introductionmentioning
confidence: 99%
“…In solution, these molecules caused strong light-induced photodamage to DNA. In some cases, pronounced dark toxicity was also observed …”
Section: Conjugation Of Photosensitizers With Cytotoxic Drugsmentioning
confidence: 97%
“…In some cases, pronounced dark toxicity was also observed. 100 The mechanism of cytotoxicity exerted by ruthenium moieties independent of a conjugated porphyrinoid has not yet fully established. Unlike platinum derivatives, ruthenium conjugates were not found in nucleus and therefore could not damage DNA.…”
Section: Cytotoxic Drugsmentioning
confidence: 99%
“…The PS forms a long-lived triplet state that can react with molecular oxygen to generate reactive oxygen species (ROS), including singlet oxygen and hydroxyl radicals, leading, in situ, to cell death by necrotic and apoptotic modes [13,14]. As a result, significant advantages of PDT on antimicrobial chemotherapy are observed: it offers a short inactivation time to lead to cell death pathways; it does not lead to bacterial resistance after multi-course treatment; it does not cause dysbacteriosis; and it is applied to a wide range of target microorganisms, including Gram-positive and Gram-negative bacteria [7,9,15]. The widespread use of PDT in the treatment of skin tumors, actinic keratosis, acne, and rosacea is noteworthy and recognized by the Brazilian Society of Dermatological Surgery.…”
Section: Introductionmentioning
confidence: 99%